Surgical management of fracture odontoid type II by anterior screw fixation: an institutional experience - Modha, Prakash (International Surgery Journal, 2022)
Fractures of the odontoid process (the dens) of the axis account for 10-20% of acute cervical spine fractures. Recent advances in intra-operative imaging including neuron avigation and O-arm can now increase accuracy and lower morbidity of odontoid screw placement. The present study was done in the department of surgery, in the medical college and associated hospital. During study period, total of 22 patients with type II fracture of odontoid were included in the study. All operations were done with the same technique of Cloward anterior approach using cannulated single lag screw. In the majority of patients, the follow up has been for 2 years and in 3 cases the follow up has been for one year. At the time of presentation, the major complains of the patient included in the study was of pain in neck area. The 14 patients were discharged to home on third postoperative day with Philadelphia neck collar, 6 patients with weakness stayed in hospital one week on physiotherapy and 2 patients were in ICU for three days post-operative due to associated lung contusion. Follow up CT after 1.5 and 3 months show well alignment with good fusion with no signs of mal union or pseudo arthrosis and patients were followed up for six months. Anterior screw fixation is a good technique to practice. It achieves good outcome and good fusion in young generation with horizontal fracture line.